Systematic Methodological Evaluation of a Multiplex Bead-Based Flow Cytometry Assay for Detection of Extracellular Vesicle Surface Signatures - Wiklander, Oscar P. B.; Bostancioglu, R. Beklem; Welsh, Joshua A.; Zickler, Antje M.; Murke, Florian; Corso, Giulia; Felldin, Ulrika; Hagey, Daniel W.; Evertsson, Björn; Liang, Xiu-Ming; Gustafsson, Manuela O.; Mohammad, Dara K.; et al. (Frontiers in Immunology, 2018)
Extracellular vesicles (EVs) can be harvested from cell culture supernatants and from all body fluids. EVs can be conceptually classified based on their size and biogenesis as exosomes and microvesicles. Nowadays, it is however commonly accepted in the field that there is a much higher degree of heterogeneity within these two subgroups than previously thought. For instance, the surface marker profile of EVs is likely dependent on the type of cell source, the cell’s activation status and multiple other parameters. Within recent years, several new methods and assays to study EV heterogeneity in terms of surface markers have been described, most of them being based on flow cytometry. Unfortunately, such methods generally require dedicated instrumentation, are time-consuming and demand extensive operator expertise for sample preparation, acquisition and data analysis. In this study, we have systematically evaluated and explored the use of a multiplex bead-based flow cytometric assay which is compatible with most standard flow cytometers and facilitates a robust semi-quantitative detection of 37 different potential EV surface markers in one sample simultaneously. First, assay variability, sample stability over time, and dynamic range were assessed together with the limitations of this assay in terms of EV input quantity required for detection of differently abundant surface markers. Next, the potential effects of EV origin, sample preparation and quality of the EV sample on the assay were evaluated. The findings indicate that the multiplex bead-based assay is generally suitable to detect, quantify and compare EV surface signatures in various sample types, including unprocessed cell culture supernatants, cell culture-derived EVs isolated by different methods, and biological fluids. Furthermore, the use and limitations of this assay to assess heterogeneities in EV surface signatures was explored by combining different sets of detection antibodies in EV samples derived from different cell lines and subsets of rare cells. Taken together, this validated multiplex bead-based flow cytometric assay allows robust, sensitive and reproducible detection of EV surface marker expression in various sample types in a semi-quantitative way and will be highly valuable for many researchers in different contexts of the EV field.